Maize Grain Stored in Hermetic Bags: Effect of Moisture and Pest Infestation on Grain Quality - Paddy Likhayo; Anani Y. Bruce; Tadele Tefera; Jones Mueke (Journal of Food Quality)
Maize (Zea mays) is an important staple food crop produced by the majority of smallholder farmers that provides household food security through direct consumption and income generation. However, postharvest grain losses caused by insect pests during storage pose a major constraint to household food security. Hermetic storage technology is an alternative method that minimises postharvest losses by depleting oxygen and increasing carbon dioxide levels within the storage container through metabolic respiration of the grains, insects, and microorganism. Maize grain was stored for 180 days in hermetic bags or open-weave polypropylene bags to compare quality preservation when subject to initial grain moisture contents of 12, 14, 16, and 18 percent and infestation by Sitophilus zeamais. The moisture content of grain in hermetic bags remained unchanged while in polypropylene bags decreased. Dry grains (12% moisture content) stored well in hermetic bags and suffered 1.2% weight loss while for equivalent grains in polypropylene bags the weight loss was 35.8%. Moist grains (18% moisture content) recorded the lowest insect density (7 adults/kg grain) in hermetic bags while polypropylene bags had the highest (1273 adults/kg grain). Hermetic and polypropylene bags recorded the lowest (0–4 adults/kg grain) and highest (16–41 adults/kg grain) Prostephanus truncatus population, respectively. Discoloured grains were 4, 6, and 12 times more in grains at 14, 16, and 18 than 12 percent moisture content in hermetic bags. Grains at 18% moisture content recorded significantly lower oxygen (10.2%) and higher carbon dioxide (18.9%) levels. Holes made by P. truncatus in the hermetic bags were observed. In conclusion, storage of moist grains (14–18% moisture content) in hermetic bags may pose health risk due to grain discolouration caused by fungal growth that produces mycotoxins if the grains enter the food chain. The study was on only one site which was hot and dry and further investigation under cool, hot, and humid conditions is required.